The Effect of Ice Breaking in Increasing Students' Learning Motivation in Elementary Schools - Ghasyiyah, Andesti Idzil; Nisa, Sahrun; Suriani, Ari (Balai Publikasi Indonesia, 2024)
This study aims to analyse the effect of using ice breaking in increasing students' learning motivation in primary schools. The research method used is a literature study with a qualitative approach that focuses on learning motivation. Identification of literature sources is done through literature searches in academic databases such as PubMed, Google Scholar, and digital libraries. The results of the analysis show that the application of ice breaking in primary school learning has a positive and significant impact on students' learning motivation. Ice breaking can restore students' concentration and make them more active, enthusiastic, and focused in learning, so that it can improve their learning outcomes. Learning motivation is an important factor in learning, because it can affect various abilities and student learning outcomes. Therefore, teachers need to understand and foster learning motivation in students through ice breaking in the learning process so that students can succeed in learning.